Knockout of reactive astrocyte activating factors slows disease progression in an ALS mouse model - Guttenplan, Kevin A.; Weigel, Maya K.; Adler, Drew I.; Couthouis, Julien; Liddelow, Shane A.; Gitler, Aaron D.; Barres, Ben A. (Nature communications, 2020)
Reactive astrocytes have been implicated in the pathogenesis of neurodegenerative diseases, including a non-cell autonomous effect on motor neuron survival in ALS. We previously defined a mechanism by which microglia release three factors, IL-1α, TNFα, and C1q, to induce neurotoxic astrocytes. Here we report that knocking out these three factors markedly extends survival in the SOD1 G93A ALS mouse model, providing evidence for gliosis as a potential ALS therapeutic target. Astrocyte activation may contribute to neurodegenerative disease. Here the authors show that the combined knockout of three factors known to promote astrogliosis, IL-1α, TNFα and C1qa, leads to improved survival in the SOD1 G93A mouse model of ALS.